Stereotactic Ablative Radiotherapy for Prostate Cancer—The Treatment Results of 500 Patients and Analysis of Failures - Miszczyk, Leszek (Technol Cancer Res Treat, 2019)
OBJECTIVE: Stereotactic ablative radiotherapy is a very promising approach for the treatment of patients with prostate cancer. The aim of this study was to evaluate the clinical tolerance, effectiveness, patterns of failure, and attempt to define predictive factors based on our experience. METHODS: The cohort consists of 264 low-risk and 236 intermediate-risk consecutive patients treated at one institution. Prostate-specific antigen (PSA), adverse effects, and androgen deprivation therapy (ADT) usage were noted. RESULTS: Median follow-up was 31.3 months. Over 90% of the patients reported no gastrointestinal toxicity. There were 4 occurrences of G3+ sequelae. 75% patients had no genitourinary toxicity at first month, and up to 90% during the rest of follow-up, with only 1 case of G3 adverse event. The toxicity was more pronounced in patients with higher PSA concentrations. Prior to stereotactic ablative radiotherapy, the mean PSA was 7.59 and 277 patients used ADT. The PSA decreased for up to 20 months before reaching a plateau. The decline was slower, and PSA levels were higher in patients without ADT. A total of 15 treatment failures occured in a median time of 19.9 months. Higher PSA concentrations were connected with higher failure rates, even in the first month and prior to reaching Phoenix criterion. CONCLUSION: CyberKnife-based stereotactic ablative radiotherapy of low-risk and intermediate-risk prostate cancer patients is an effective and well-tolerated modality of treatment. PSA is the most important predictive factor. The evolution of PSA concentration in a particular subgroup of patients suggests that ADT in intermediate-risk cases could improve long-term results.